2009
DOI: 10.1111/j.1365-2613.2009.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with sildenafil stimulates Leydig cell and testosterone secretion

Abstract: The phosphodiesterase type 5 (PDE5) inhibitor, Sildenafil, is a novel, oral treatment approach for pulmonary hypertension. As Leydig cells present PDE5, this study was conducted to investigate the effects of the chronic treatment with Sildenafil (25 mg/kg) on male Swiss Webster mice steroidogenesis. After a 4-week long experimental design, Leydig cells were analysed by morphological and immunocytochemical procedures. Serum testosterone was assayed by radioimmunoassay. Leydig cells presented noteworthy ultrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 42 publications
2
33
1
3
Order By: Relevance
“…Prolonged PDE5i in rats stimulates Leydig cell steroidogenesis, through a coordinate stimulatory effect of cAMP and cGMP (31). Both of these messengers act synergistically and converge on steroidogenic acute regulatory protein to enhance testosterone production (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged PDE5i in rats stimulates Leydig cell steroidogenesis, through a coordinate stimulatory effect of cAMP and cGMP (31). Both of these messengers act synergistically and converge on steroidogenic acute regulatory protein to enhance testosterone production (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular level of cGMP is controlled by cGMP-selective phosphodiesterases (PDEs), expressed in Leydig cells (1,2,20,33) and inhibition of Leydig cell PDE5 in vitro, were accompanied by elevations of cGMP and testosterone production (1). Additionally, in mice, chronic inhibition PDE5 caused ultrastructural changes characteristic for secretory active Leydig cells (31).…”
mentioning
confidence: 99%
“…Moreover, the changes in the testosterone level in experimental animals treated with sildenafil were controversial in previous studies [21][22][23][24]. Janjic et al [21] demonstrated that the serum testosterone level was increased in male adult rats at 60 and 120 min after the oral administration of sildenafil (1.25 mg/kg), which was a transient rise.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of sildenafil on testosterone production was investigated in a few previous studies [21][22][23][24], whereas that on the 17β-estradiol level has been little studied. Moreover, the changes in the testosterone level in experimental animals treated with sildenafil were controversial in previous studies [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%